Metabolic cost of running barefoot versus shod: is lighter better? - Franz, J. R.; Wierzbinski, C. M.; Kramer, R. (Medicine & Science in Sports & Exercise, 2012)
Purpose: Based on mass alone, one might intuit that running barefoot would exact a lower metabolic cost than running in shoes. Numerous studies have shown that adding mass to shoes increases submaximal oxygen uptake (VO2) by approximately 1% per 100 g per shoe. However, only two of the seven studies on the topic have found a statistically significant difference in VO2 between barefoot and shod running. The lack of difference found in these studies suggests that factors other than shoe mass (e.g., barefoot running experience, foot strike pattern, shoe construction) may play important roles in determining the metabolic cost of barefoot versus shod running. Our goal was to quantify the metabolic effects of adding mass to the feet and compare oxygen uptake and metabolic power during barefoot versus shod running while controlling for barefoot running experience, foot strike pattern, and footwear.